INOVASI DAN SENI PADA VALUE ENGINEERING UNTUK PENGELOLAAN KONSTRUKSI - Kazan Gunawan (Jurnal Sosioteknologi, 2006)
The success of a project is often evaluated on the basis of the cost amount the project has spent and the punctuality of completing the project. In effect, such aspect as how the project executor is able to interpret the asset user's interest to do his/her business activities successfully in the project is frequently unobserved. This project executor's interpretation ability can be seen from the project design he/she creates to meet his/her customer's satisfaction, for example comfotable atmosphere and function fulfilment of the project. Therefore, to enable an architecture meets the customer up-to-date needs, the enhancement of the Value engineering and innovation to find the lowest cost, easy to implement, and fast method is needed. Monte Carlo Simulation has been used for explaining the method.